2015
DOI: 10.1371/journal.pone.0116057
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Organic Pollutants and Early Menopause in U.S. Women

Abstract: ObjectiveEndocrine-disrupting chemicals (EDCs) adversely affect human health. Our objective was to determine the association of EDC exposure with earlier age of menopause.MethodsCross-sectional survey using National Health and Nutrition Examination Survey (NHANES) data from 1999 to 2008 (n = 31,575 females). Eligible participants included: menopausal women >30 years of age; not currently pregnant, breastfeeding, using hormonal contraception; no history of bilateral oophorectomy or hysterectomy. Exposures, defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(81 citation statements)
references
References 40 publications
2
77
0
2
Order By: Relevance
“…With intermediate (45)(46)(47)(48)(49)(50)(51)(52)(53)(54) and premutation carriers (55-200 CGG repeats), we notice a translation fault which can be held accountable for mRNA production levels [93] not balanced through an equivalent rise in FMRP that frequently is normal or somewhat reduced. By consequence, the mRNA levels build-up in the cells where it is hypothesized to exert cytotoxic effects (RNA/protein toxic gain-of-function disorder).…”
Section: How Fmr1 Mutations Influence Different Phenotypesmentioning
confidence: 83%
See 2 more Smart Citations
“…With intermediate (45)(46)(47)(48)(49)(50)(51)(52)(53)(54) and premutation carriers (55-200 CGG repeats), we notice a translation fault which can be held accountable for mRNA production levels [93] not balanced through an equivalent rise in FMRP that frequently is normal or somewhat reduced. By consequence, the mRNA levels build-up in the cells where it is hypothesized to exert cytotoxic effects (RNA/protein toxic gain-of-function disorder).…”
Section: How Fmr1 Mutations Influence Different Phenotypesmentioning
confidence: 83%
“…This 'normal' range, however, may not in fact be a homogenous population. Gleicher et al reported the intermediate genotype (45)(46)(47)(48)(49)(50)(51)(52)(53)(54) repeats) expresses a minor instability unrelated to a definite phenotype or to the fragile X syndrome (FXS) within one generation, even though the risk is consistent in two generations [113]. These intermediate carriers, compared to 'normal', show a greater prevalence of subfertility, menstrual cycle anomalies, overall earlier than anticipated menopause (by ∼7 years), premature ovarian failure (32 vs 1 %), increased prevalence of osteoporosis, higher rate of aneuploidy, miscarriage and even perhaps non-identical twinning rates [85,94].…”
Section: The Cgg Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to ovarian aging outcomes in particular, a recent review [95] summarized relevant human and animal literatures, suggesting environmental toxicants accelerate folliculogenesis and follicular atresia, including in the primordial stage and extending across the spectrum of ovarian follicle development. Notably, in a large representative sample of US women (n = 31,575) EDCs (i.e., polychlorinated biphenyl [PCBs], pesticides, furans, and phthalates) were associated with earlier onset menopause up to 3.8 years earlier, following adjustment for covariates [96]. In addition, prospective studies showed higher urinary phthalate and BPA levels were related to decreases in ovarian reserve as marked by lower AFC, although participants were patients seeking infertility treatment [97,98].…”
Section: Discussionmentioning
confidence: 99%
“…The association between environmental chemical exposure and endocrine abnormalities, including early menopause, has previously been suggested 4. One presumptive trigger, BPA is a chemical used in the production of plastics and epoxy resin.…”
Section: Discussionmentioning
confidence: 99%